0966 Navigating the Path to Primary Care Involvement in the Care of Stable Obstructive Sleep Apnea Patients. (12th April 2019) - Moore, Wendy R; Mansukhani, Meghna P; Harris, Cameron; Kakkar, Gurnoor S; Herold, Daniel L; Williams, Julie A; Cleveland, Eric J; Morgenthaler, Timothy I
Abstract: Introduction: Follow-up care of patients with obstructive sleep apnea (OSA) on positive airway pressure (PAP) therapy has become increasingly complex due to regulatory requirements and primary care provider experience in this area may be limited. We present a project aimed to facilitate primary care management of stable PAP users at our institution. Methods: A multidisciplinary workgroup of key stakeholders was formed with representation from sleep medicine and primary care, including physicians, a nurse manager, operations administrator, laboratory supervisor, appointment office manager and financial analysts. The group evaluated existing patient volumes and workflows for chronic management of OSA. Analyses reflected a very high rate of established patients returning for follow-up (76%); of these 64% were stable OSA patients on PAP treatment who were not receiving specialized or new interventions. As a tertiary sleep center practice, it seemed most practical to develop a care pathway for patients with established primary care services within our institution. Our group established criteria for identification of stable OSA patients on PAP therapy that could be transitioned back to primary care. A care process model was developed for provider reference. Relevant educational material relating to PAP download reports, PAP troubleshooting, prescription requirements/insurance visit guidelines and reasons for referral back to sleep medicine, were placed on the institutional website. Communication plans were developed and methodology for transfer of care implemented. Results: Initial implementation of the project resulted in an increase of 6 new consultation appointments a week (312/year) at the sleep center and a 14% reduction in follow-up appointments with a projected financial improvement of $263, 841/year. Primary care teams were hesitant about assuming responsibility for long-term care of OSA and patients accepted the transition. Conclusion: With the growing number of patients requiring longitudinal care for OSA, it is imperative to explore how and when transitions from sleep specialty services to primary care should occur. This project proposes steps to standardize the process and collaborate effectively with primary care colleagues; thereby assuring patients achieve competent care in the transition. Support (If Any)